PENGAMALAN DAN PENGELOLAAN ZAKAT BERBASIS KEARIFAN LOKAL (STUDI DI MASYARAKAT KAMPUNG SANGGAU) - Hasan, Muhammad (al-'adalah, 2015)
Abstract: Practice and Zakat Management Based Local Wisdom (Studies in Society Sanggau Villagers). This article reviews the model of practices and management of zakat (alms) among the Sanggau villagers. In the community, zakat is no longer regarded merely as an obligation set by religion, but it has become a necessity in the life of the society. When someone harvests, neighbors do not ask about how many crops he/she obtained, but ask how much zakat issued of the crop. Uniquely, apart from the fact that the villagers are not bound to the rules of zakat implementation, such as: mustahik (group of recipients), aul (time limit), nisab (quantity limit), and amounts, they appoint the amil (commitee) of zakat based on asnaf mustahik (the group of recipients) in the community. Although the management system sounds simple, but the pattern of practices is really modern. Because of such a model and management style, the awareness of paying zakat is very high in this community.Keywords: management of zakat, tradition among the Sanggau villagersAbstrak: Pengamalan dan Pengelolaan Zakat Berbasis Kearifan Lokal (Studi di Masyarakat Kampung Sanggau). Artikel ini mengulas model pengamalan dan pengelolaan zakat di masyarakat kampung Sanggau. Bagi masyarakat tersebut, zakat tidak lagi dipandang semata-mata sebagai suatu kewajiban yang ditetapkan oleh agama, melainkan telah menjadi suatu kebutuhan dalam kehidupan bermasyarakat. Ketika seseorang memperoleh hasil panen, tetangganya tidak menanyakan mengenai seberapa banyak hasil panen yang diperoleh, tetapi menanyakan seberapa banyak zakat yang dikeluarkan dari hasil panennya. Uniknya lagi, selain dari masyarakat tidak begitu terikat pada kaidah-kaidah pelaksanaan zakat, seperti: penerima, aul, nisab, dan kadarnya, dalam pengangkatan amil merekapun menggunakan model asnaf mustahik. Meskipun sistem pengelolaannya sederhana, namun pola manajemen yang mereka praktikkan nampak modern. Karena model dan gaya pengelolaan yang seperti ini, kesadaran berzakat pada komunitas ini sangat tinggi.Kata Kunci: pengelolaan zakat, tradisi masyarakat kampung Sanggau